BENTUK PENYAJIAN TARI KONCONG DI DESA BABANE KECAMATAN SAMALANTAN KABUPATEN BENGKAYANG - Azizah, Nur; Fretisari, Imma; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research analyzed about the form of Koncong Dance performance inBabane Village, Samalantan District, Bengkayang Regency. The purpose of this research were, Describing the elements of the persentation in composition Koncong Dance performance and describing the contribution of the results of the Koncong Dance as a learning media in Art and Culture subject on Eighth Grade Students at Junior High School. Method with using qualitative research as the research design and used choreographic approach as the research approach. The data collecting techniques of this research were using observation, interview and documentation. The researcher applied an extension of observation and triangulations. Technique to test the validity of the data. Koncong Dance had a form of performance that consists of initial motion, middle, and closing. Other elements contained in other forms of performance were,Floor design, group composition, the theme, accompaniment, make up and clothing, place of performance. The results of this research was expected to be contributed as material for the learning media in the form of video performances at the Art and Culture subject on class VIII students Junior High School.Keywords: Babane Village, Form of Performance, Koncong Dance,Samalantan District